Seismic reflection imaging over the South Portuguese Zone fold-and-thrust belt, SW Iberia - Schmelzbach, C.; Simancas, J.; Juhlin, Christopher; Carbonell, R. (Wiley-Blackwell Publishing, 2008)
We reprocessed an ~35-km-long part of the IBESREIS seismic reflection profile which runs over the Iberian Pyrite Belt section of the South Portuguese Zone, SW Iberia, with the goal to image the upper crust, (<15-km depth). The applied processing sequence enhanced numerous prominent reflections and diffraction patterns within the uppermost 5-s travel time relative to high-amplitude source-generated noise. A complex subsurface characterized by conflicting dips and a survey following winding roads require a crooked-line prestack migration scheme for coherent imaging. To interpret sources of diffracted energy, we additionally employed a diffraction imaging scheme which enhances diffractions at the expense of reflections.The final seismic images show south-vergent imbricate fold-and-thrust tectonics, documenting the contractive deformation that the South Portuguese Zone experienced during the Variscan Orogeny. Based on surface geological information, we correlate a low reflective unit with the shallow Upper Carboniferous Flysch Group, a highly reflective unit ranging in depth from 2 to 4 km with the Middle Carboniferous Volcano-Sedimentary Complex Group, which hosts massive sulfide deposits, and a moderately reflective unit with the Upper Devonian Phyllite-Quartzite Group. Below these units, another low-reflective facies is present, which may represent older Paleozoic metasediments. In addition, the seismic and diffraction images reveal bands of high reflectivity and distinct diffraction patterns that were interpreted as extensive layered mafic intrusions. These proposed mafic bodies may be related to the same event that triggered a huge hydrothermal activity assumed in Early Carbonifereous times. Copyright 2008 by the American Geophysical Union.